Faktor-Faktor yang Mempengaruhi Minat Pengguna Jasa Taksi Online - Purnomo Ari Wibowo; Helmi Alam Hibatullah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
In this study, three research variables were analyzed: service, price perception, and facilities as independent variables that influence the dependent variable, namely service user interest in users of the Gojek online-based taxi service in Semarang. The formulation of the problem, research objective and hypothesis in this study is to analyze the positive and significant influence individually between the independent variables, namely service quality, perception of risk and promotion on the dependent variable, namely the interest of online study taxi service users on Gojek customers in Semarang. The objects taken were users of the online Gojek based taxi service in Semarang. Data sources include primary and secondary data. The results of the multiple linear regression equation show that there is a positive and partially significant influence between service quality on service user interest (t-count 2.163 > t-table = 1.98447), perception of risk on service user interest (t-count = 5.657 > t-table = 1.98447 ), promotion of service user interest (t count = 4.859 > t-table = 1.98447) while the coefficient of determination gets an R square value of 0.547.